Prevention and treatment of diabetic foot - Valčiukienė, Lina; Stauskienė, Kristina; Urbonienė, Laima (Slauga. Mokslas ir praktika, 2023)
People with diabetes often have foot problems. If not prevented, diabetic feet develop wounds, deformities and infections, making treatment lengthy and costly for the healthcare system. Diabetic foot is a fast-growing chronic complication of diabetes and has been diagnosed in more than 400 million people worldwide. More than 85% of affected people have had their lower limbs amputated as a result of this condition.Although health professionals and researchers have paid little attention to effectively addressing this problem compared to treating diabetic foot, preventing diabetic foot is an excellent way to prevent the severe morbidity and mortality of people with diabetes.The aim of the study is to analyse the prevention and treatment of diabetic foot on the basis of a systematic review of the scientific literature.Materials and methods. The type of study was a systematic literature review. The systematic literature review was conducted using the PRISMA (Perffered Reporting Item for Systematic Reviews and MetaAnalyses) method. For the systematic literature review, publications were searched for in the virtual electronic databases Pub Med and Google Scholar. The search used terms relevant to the aim of the study (diabetic foot, diabetic foot ulcer, treatment, complications, prevention). Twenty (n=20) full articles meeting the eligibility criteria were included in the systematic review of the scientific literature.
Keywords: diabetic foot; diabetic foot ulcer; treatment; complications; prevention